Circulatory Level of Endothelin-1 and Hypertension in Rural Women in Bangladesh: A Potential Association Evidenced From a Community Based Cross-Sectional Study. (June 2015) - Rahman, Md. Arifur; Jesmin, Subrina; Islam, Md. Majedul; Sohael, Farzana; Hasan, Ammar Shaker Hamed; Zaedi, Sohel; Sultana, Sayeeda Nusrat; Yamaguchi, Naoto; Kawano, Satoru; Okazaki, Osamu; Habib, A.K.M. Ahsan
Abstract : Objective: High blood pressure is one of the primary risk factor for heart disease, stroke and chronic kidney disease and the leading cause of death worldwide. About 20% of adult populations are hypertensive in Bangladesh. Endothelin-1 (ET-1), a potential marker of endothelial dysfunction has been shown to be elevated in hypertensive subjects. No study yet has investigated the circulatory level of ET-1 and hypertension in a country from South Asia. As racial differences exist in plasma level of ET-1, more research addressing the association between ET-1 and hypertension among other races needs to be investigated. As such, the present study assessed circulating levels of ET-1 in subjects with or without hypertension and further examined the association of ET-1 with clinical and metabolic parameters. Methods: A total of 2052 rural Bangladeshi women with mean age of 44.46years were studied using a cross-sectional survey. Multiple regressions were used to examinethe association between circulatory ET-1 level and hypertension. Results: The prevalence of hypertensionwas30.3%. ET-1 levels were significantly higher in hypertensive (mean 3.08 pg/ml, SE ± 0.19) than non-hypertensive subjects (mean 2.01 pg/ml, SE ± 0.30) ( p = <0.001). In univariateanalysis after adjusting for age, ET-1 had significant positive associations with diastolic blood pressure (DBP) ( p = 0.002), systolic blood pressure (SBP) ( p = <0.001), fasting blood glucose ( p = 0.002), mean arterial pressure (MAP) ( p = 0.001)and a negative significant association with high-density lipoprotein cholesterol (HDL) ( p = 0.030). Unlike blood pressures, other variables including, triglycerides, body mass index, and waist circumference were not associated with ET-1. In multiple linear regression analysis after adjusting for age, ET-1 had significant positive associations with fasting blood glucose (p = 0.012) and mean arterial pressure (MAP) ( p = 0.05)only. When we performed multiple logistic regression analysis considering hypertension status as dependent variable, hypertensive had significant positive associations with age ( p = 0.015), waist circumference ( p = <0.001), fasting blood glucose ( p = 0.009), triglyceride ( p = 0.001) and endothelin-1 (0.026). In tertile analysis, subjects with hypertension significantly increase as levels of ET-1 increase (P for trend = 0.02). Conclusions: Thus the present study demonstrates that there is higher concentration of ET-1 among hypertensive subjects of apparently healthy population in Bangladeshi rural women who did not know they were hypertensive. The relation of ET-1 and hypertension needs further investigations to define the clinical utility and predictive value of serum ET-1 levels in hypertension for South Asian population.